A study of incidence, risk factors, clinical profile and management of 50 cases of ectopic pregnancy in a tertiary care teaching hospital - Ganitha, G.; Anuradha, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is a challenging and life-threatening emergency, which can cause significant maternal morbidity and mortality. The present study aims at determining the incidence, risk factors, clinical features, diagnosis, management and outcome of ectopic pregnancies in a tertiary care teaching hospital. Methods: This was a prospective study of 50 cases of ectopic pregnancies admitted to the Department of Obstetrics and Gynaecology at a tertiary care teaching hospital from August 2012 to September 2013. Relevant data of the 50 patients was tabulated and descriptive analysis was carried out. Results: The incidence of ectopic pregnancy was 6.3 per 1000 deliveries. Majority of the patients (82%) belonged to 20-30 yrs age group. 70% of the women were multiparous. The commonest site of ectopic pregnancy was fallopian tube (92 %). Past history of pelvic inflammatory disease (40%), abortions (20%), abdominopelvic surgery (14%) and IUCD usage (12%) were among the important risk factors identified. 20% of the patients had no identifiable risk factor. The classical triad of amenorrhea, bleeding per vaginum and abdominal pain was seen in 56 % of the study population. The most important signs which guided the diagnosis of ectopic pregnancy were cervical excitation pain (74%), abdominal tenderness (72%), adnexal mass or fullness (68%) and tenderness in the fornix (68%). Clinical presentation, urinary pregnancy test, culdocentesis and ultrasound were the diagnostic tools used for diagnosis of ectopic pregnancy. The incidence of ruptured ectopic pregnancy was 86%. Majority of the patients underwent salpingectomy (96%). There was no maternal mortality in our study. Conclusions: Early diagnosis, timely referral, improved access to health care, aggressive management and improvement of blood bank facilities can reduce the maternal morbidity and mortality associated with ectopic pregnancy.